PENERAPAN METODE FUZZY K-NEAREST NEIGHBOR (FK-NN) UNTUK MENENTUKAN PENYAKIT PADA TERNAK SAPI POTONG - Malelak, Yohanis; Tomasoey, Junandra H (STIKOM Uyelindo Kupang, 2019)
Cattle are one of the livestock commodities that are a mainstay as a source of protein. Animal is meat that is quite well known in the community. Decent meat taken from healthy livestock and free from diseases caused by diseases suffered by cattle must be handled seriously. Beef cattle breeders in East Nusa Tenggara, especially young cattle breeders, are hard to find by medical personnel such as compilation veterinarians to find sick cattle. On the other hand, the Livestock Service Office of NTT Province annually collects cattle disease data to draw conclusions about animal diseases in the regency / city in East Nusa Tenggara. Through data from the Kupang District Animal Husbandry Service, East Nusa Tenggara with data mining techniques can predict livestock disease using the Fuzzy K-Nearest Neighbor (FK-NN) algorithm. Fuzzy K-Nearest Neighbor (FK-NN) algorithm works by receiving input of diseases as input, then it will be processed with FK-NN algorithm and the results of processing become diagnoses of diseases suffered and therapeutic suggestions for diseases in beef cattle So it can increasing the yield of beef collected from beef cattle and minimizing the costs incurred by cattle farmers to care for infected livestock to consult with veterinarians.